ANALISIS HUKUM ISLAM TERHADAP HUBUNGAN BADAN SUAMI ISTRI DALAM MASA KAFARAT ZHIHAR - Siti Mar’atus Shoolihan; Fashihuddin Arafat (MIYAH : Jurnal Studi Islam, 2021)
Zhihar means that a husband equates his wife with his mahram in matters relating to sexual relations. As the husband said: "To me you are like my mother". The husband's speech towards his wife is based on the intention to forbid his wife, then zhihar for him falls. Zhihar is haraam according to the agreement of ulama. This is based on the word of Allah found in QS. Al-Mujadalah verse: 3. A person who has persecuted his wife, then he may not intercourse with his wife, until he has paid the prescribed kafarat. The zhihar kafarat includes freeing a slave or obliging to fast for two consecutive months or obliged to feed sixty poor people. In this journal, the writer intends to describe how the Islamic viewpoint is if husband and wife intercourse is carried out during the kafarat period? What are the sanctions for a husband who intercourse with his wife before the zhihar kafarat is completed? Library research (library research) is chosen by the writer in dealing with this problem. The Ulama have agreed that if the intercourse is carried out before the husband completes his zhihar kafarat, then the relationship is haraam and for this violation there is no additional sanction for him, it is enough to pay the kafarat as prescribed.Keywords : Kafarat, Zhihar, Islamic Law